A SOCIOLINGUISTIC ANALYSIS OF TABOO WORD CHARACTER IN MILKMAN NOVEL: Sociolinguistics, Taboo, Milkman Novel - Muhammad Ainul Yaqin (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2021)
Sociology is the objective and scientific study of humans in society, and of the social institutions and processes that exist in society. Linguistics is a field of science that studies language, or a field of science that takes language as its object of study. In sociolinguistics, taboo words are part of sociolinguistics related to language and society. The word taboo is a word that is not considered good by the public or is better avoided, because they mention facts that are considered rude and disrespectful, in this study using a literature study taken from the milkman novel using reading techniques and marking parts of the word taboo in novel and the results obtained are obsenity 4 taboo sentences, profanity 2 taboo sentences, vulgarity 3 taboo sentences, epithet 1 taboo sentence, and taboo sentences in milkman novels are sentences that are usually spoken to insult or give nicknames to others.